GAMBARAN BODY IMAGE PADA SISWA KELAS XI SMAN 1 MARGAASIH - Aep Saepudin; Wahyu Hidayat; Ecep Supriatna (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
This study intends to explain how the level of body image in class XI students at SMAN 1 Margaasih. The number of samples used as many as 140 students from a total population of 355 students, or if described 87 female students and 53 male students. Among them there are 22% of students aged 17 years, 68% of students aged 16 years and 10% of students aged 15 years. This study uses a descriptive quantitative approach with a random sampling technique. The data collection instrument used was a non-test technique in the form of a questionnaire taken from Maulida (2020). In this study, it was found that the body image of class XI students of SMAN 1 Margaasih was generally in the medium category or as much as 72% (101 students), while in the high category it was 16% (23 students), and the low category was 12% (16 students). . The data obtained shows that female students have body image a lowerthan male students. This can be explained by the presence of 16 students who are categorized as low body image, 14 of whom are female students. This is because women generally have body image a lowerthan men. An example that can be seen is the feeling of inferiority to their physical possessions and often comparing themselves with others who have more physicality than them. The physical can be in the form of height, weight, attractive face, and skin color.Keywords: Body image, Students, SMAN 1 Margaasih